Unexplained Findings of Kayser-Fleischer-Like Rings in a Patient with Cryptogenic Cirrhosis - Mahreema Jawairia; Miral Subhani; Ghulam Siddiqui; Apsara Prasad; Ghulamullah Shahzad; Kaleem Rizvon; Paul Mustacchia (Case Reports in Gastrointestinal Medicine)
Cryptogenic cirrhosis (CC) is defined as cirrhosis occurring in an individual without an identifiable cause of liver disease, such as excessive alcohol consumption, viral hepatitis infection, hemochromatosis, autoimmune hepatitis, primary biliary cirrhosis, primary sclerosing cholangitis, chronic intake of medications that could induce cirrhosis, alpha-1-antitrypsin deficiency, Wilson’s disease, or any other rare cause of cirrhosis according to the clinical context. Cryptogenic cirrhosis is a common cause of liver-related morbidity and mortality in the United States. Nonalcoholic fatty liver disease is now recognized as the most common cause of cryptogenic cirrhosis. A biopsy specimen is also important for detecting histological advanced disease, which may be clinically silent and undetected by liver-related tests or diagnostic imaging. We are presenting an unusual case of a patient with cryptogenic cirrhosis found to have Kayser-Fleischer-like rings without evidence of Wilson’s disease.